1988
DOI: 10.1139/f88-044
|View full text |Cite
|
Sign up to set email alerts
|

Fish in the Structure and Function of Freshwater Ecosystems: A "Top-down" View

Abstract: The role of fish in regulation of the structure and function of freshwater ecosystems (lakes and streams) is examined with respect to effects resulting directly from their feeding activity, indirectly from size or other forms of prey selectivity, and from influences on nutrient cycling and transport. That fish have long had a legitimate place in limnological research is documented by a review of limnological books, texts, and journals. Recognition of their "top-down" effects, started largely from Czechoslovaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
143
0
6

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(156 citation statements)
references
References 39 publications
7
143
0
6
Order By: Relevance
“…Fish significantly decreased cladoceran densities and Secchi depths and increased turbidity and chlorophyll. In general, these effects of mosquitofish on zooplankton and phytoplankton are typical of visually feeding fish (Lazzaro 1987;Northcote 1988) and are similar to the results of pool and pond experiments of Hurlbert et al (1972) and Hurlbert and Mulla (198 1). Hurlbert et al (1972) found that mosquitofish presence increased total phosphorus, but they used a higher density of mosquitofish (-50 large fish m-'); we used smaller fish stocked at -4 fish me3.…”
Section: Acknowledgmentssupporting
confidence: 74%
See 1 more Smart Citation
“…Fish significantly decreased cladoceran densities and Secchi depths and increased turbidity and chlorophyll. In general, these effects of mosquitofish on zooplankton and phytoplankton are typical of visually feeding fish (Lazzaro 1987;Northcote 1988) and are similar to the results of pool and pond experiments of Hurlbert et al (1972) and Hurlbert and Mulla (198 1). Hurlbert et al (1972) found that mosquitofish presence increased total phosphorus, but they used a higher density of mosquitofish (-50 large fish m-'); we used smaller fish stocked at -4 fish me3.…”
Section: Acknowledgmentssupporting
confidence: 74%
“…The biomass and species composition of plankton are regulated by the availability of nutrients, principally phosphorus (McQueen et al 1986;Smith 1983). Planktonic community structure can also be affected through predation by planktivorous fish (Lazzaro 1987;Northcote 1988).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Furthermore, it has often been reported that fish such as tilapia, by recycling nutrients through excretion, eventually promote the production of phytoplankton in ponds and lakes (McQueen et al, 1986;Drenner et al, 1987;Lazzaro, 1987;Northcote, 1988;Elser et al, 1990). Without algal biomass control, an excessive algal bloom may occur, followed by a collapse of the algal population, an increase in ammonia concentration and an oxygen depletion (Rimon and Shilo, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, because predation by visually foraging piscivorous fishes can affect the structure and function of aquatic communities (Paine, 1966;Northcote, 1988), changes in the visual environment may thus have far-reaching effects on coastal ecosystems and their management through light-induced changes in picscivore behavior (Aksnes, 2007). However, visual function of coastal piscivorous fishes has received relatively little attention despite their importance to both commercial and recreational fisheries.…”
Section: Introductionmentioning
confidence: 99%